The Effectiveness of Citizenship Education (PPKn) Module on Environmental Love Material by Using Example Non Example Learning Model - Sari Jusnita Br Ginting; Dede Ruslan; Arif Rahman (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study deals with the effectiveness of citizenship education (PPKn) module on environmental love material by using example non example learning model. This research uses the type of Research and Development research. The population in this research and development are all grade II students of SD Negeri 040446 Kabanjahe. The sample set in this study amounted to 28 students. The Development of PPKn Module on environmental love material by using the example non example learning model in increasing the learning activities of Grade II students of SD Negeri 040446 Kabanjahe by using the Borg and Gall development model (in Tegeh et al, 2014: 7-13) also meet valid criteria, and be effective in their use in learning activities and enhance student learning activities. It concludes that learning using PPKn module on environmental love using the example non example learning model is better than before.